Value Stream Mapping sebagai Alat Identifikasi Waste Â¬ pada PT. X untuk Departemen A - Yulianto, Joko; Octavia, Tanti (Jurnal Titra, 2013)
PT. X is one of company that concerns with continuous improvement.Â PT. X attempts to apply the concept of lean manufacturing in order to identify waste. Value stream mapping is one of the tools from lean manufacturing that can illustrate the entire process and identify waste ranging from the arrival of raw materials to the delivery of finished goods. Value stream mapping will be carried out at PT. X for department A. Through the current state value stream mapping can be seen that there are some waste in PT. X for department A ranging from the arrival of raw materials to become finished goods, among others is waste motion, over-processing waste, defect waste, inventory waste, and waste waiting. Design of future state value stream mapping is based on the proposed improvement given to the company. Future state value stream mapping can reduce lead time 41% from the current state value stream mapping.